Smartphone Recommendations Based on Specifications Using Fuzzy Tahani - Qadri, Zul; Maolani, Muh. Alfi; Awaluddin, Muh. Ghazali; Adiba, Fhatiah; Nasurullah, Asmaul Husna (Jurnal Media Informasi Teknologi, 2025)
Technology has become an integral part of people's lives, especially smartphones. Smartphones are needed nowadays because of their very complete functions and features. Due to the large number of users, manufacturers compete to create smartphones with various features and prices. Often, the large number of cell phones available makes users confused about choosing a smartphone. So calculations and comparisons are needed from various sides so that users don't make the wrong choice. Therefore, this research proposes a method of calculating and comparing smartphones based on fuzzy logic with the resistance method through a system created by researchers. These calculations and recommendations rely on information from market demand through researchers who are also smartphone market players, so they can provide recommendations that are quite accurate and by conditions that often occur in the market. With this recommendation system, users can easily search for the cellphone they want, coupled with the fuzzy logic calculation method, which makes this system's calculations more accurate, thereby preventing user choice errors. With this, users also get a comparison of recommendations that will help them choose the smartphone they want.